2007
DOI: 10.1111/j.1475-682x.2007.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

It's the Message, Not the Messenger: The Declining Significance of Black–White Contact in a “Colorblind” Society*

Abstract: 358 EILEEN O'BRIEN AND KATHLEEN ODELL KORGEN racism" or "laissez-faire" racism. These scholars alerted us that survey results trumpeting declining levels of prejudice were not telling the whole story. For example, Kinder and Sears (1981) coined the term "symbolic racism" to describe the contradiction they found in their survey results whereby respondents supported ideals of equal opportunity regardless of race, but did not support public policy measures which would bring about such equality. More recently, Bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…Without thoughtful and careful mediation, cross-cultural experience can be miseducative in that, as prospective teachers encounter differences that challenge their values and beliefs, it is possible to create resistance (LevineRasky, 2000;Trainor, 2002;Wagner, 2005), reinforce bias and privilege, or simply assimilate oppressive beliefs within existing systems (O'Brien & Korgen, 2007). Thus, carefully designed mediation of experience is essential (Brown, 2004;Burant & Kirby, 2002;Emmanuel, 2005).…”
Section: Mediating Multicultural Competence and Critical Consciousnessmentioning
confidence: 97%
“…Without thoughtful and careful mediation, cross-cultural experience can be miseducative in that, as prospective teachers encounter differences that challenge their values and beliefs, it is possible to create resistance (LevineRasky, 2000;Trainor, 2002;Wagner, 2005), reinforce bias and privilege, or simply assimilate oppressive beliefs within existing systems (O'Brien & Korgen, 2007). Thus, carefully designed mediation of experience is essential (Brown, 2004;Burant & Kirby, 2002;Emmanuel, 2005).…”
Section: Mediating Multicultural Competence and Critical Consciousnessmentioning
confidence: 97%
“…Recently with the "hiring" of the first black President, that accusation has become void of any credibility. (902) Scholars have suggested that minimization claims reduce perceptions that racism still functions, which frames instances of racism as rare, isolated incidents that are deemed as fluke occurrences (Bonilla-Silva, 2003;O'Brien & Korgen, 2007). Although this became manifest in the data, it was also interesting that people pointed to Barack Obama's election to the United States presidency as evidence that racism had diminished.…”
Section: Transferencementioning
confidence: 99%
“…Consistent with McAdam's (1988) research on the 1960s civil rights workers, some contemporary white antiracists also become involved through activist networks – their activist friends invite them to a meeting or a workshop (O’Brien 2001). Some become involved because their religious organization is committed to issues of social justice – one person's church even had an ‘antiracism committee’ (O’Brien and Korgen 2007). Still, others reported an influential college class, book read, song heard, or lecture attended (O’Brien 2001).…”
Section: What Conditions Tend To Foster Antiracism?mentioning
confidence: 99%